Immunohistochemical Expression of CXCR4 on Breast Cancer and Its Clinical Significance. (16th June 2015) - Okuyama Kishima, Marina; Oliveira, Carlos Eduardo Coral de; Banin-Hirata, Bruna Karina; Losi-Guembarovski, Roberta; Brajão de Oliveira, Karen; Amarante, Marla Karine; Watanabe, Maria Angelica Ehara
Abstract : Many tumor cells express chemokines and chemokine receptors, and, for this reason, these molecules can affect the tumor progression. It is known that breast cancer is a complex and heterogeneous neoplasia comprising distinct diseases, histological characteristics, and clinical outcomes. The most studied role for CXCL12 chemokine and its receptor CXCR4 in breast cancer pathogenesis is the metastasis event, although several reports have demonstrated its involvement in other processes, such as angiogenesis and tumor growth. It has been found that CXCR4 is required for breast cancer cell migration to other sites such as lung, bone, and lymph nodes, which express high levels of CXCL12 chemokine. Therefore, CXCR4 is being considered a prognostic marker in breast cancer. Within this context, this review summarizes established studies involving expression of CXCR4 on breast cancer, focusing on its clinical significance.